Pathology of the reproductive system of Japanese Quails (Coturnix coturnix japonica) - Sivakumar V (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 2003)
The present study was undertaken to assess the prevalence and pathology of various diseases affecting the reproductive system of Japanese quails. The data collected from the autopsy records maintained at the Centre of Excellence in Pathology, Mannuthy and one hundred and two samples of reproductive organs obtained from the necropsy cases formed the basis of the study. Retrospective survey revealed the increasing incidence of the reproductive diseases. Out of the 1139 cases encountered, various reproductive diseases were seen in quails at an incidence rate of 25.11 per cent. Oophoritis was the most prevalent among them at an incidence rate of 9.46 per cent. The higher incidence of reproductive diseases could be attributed to the maintenance of large number of breeder stock in the quail farm, which formed the major source for the necropsy samples. The gross and histopathological examination revealed that among the reproductive diseases the highest mortality was due to oophoritis (12.64 per cent) followed by egg bound (11.75 per cent). Other cases were salpingitis, egg impaction, ovarian fibroma, testicular hypoplasia and orchitis. Escherichia coli, Klebsiella and Proteus were isolated from various cases. The incidence of pathological disorders encountered was relatively high. The need and scope for investigation into the diseases affecting quail reproductive system were highlighted.